AN ANALYSIS ON THE STUDENTS' ERROR IN WRITING REPORT TEXT AT EIGHT GRADE STUDENTS OF SMP N 6 TIMANG GAJAH - Muhammad Hasyimsyah Batubara; Cut Dara Ilfa Rahila; Putri Rahmadani (Asosiasi Dosen Perguruan Tinggi Islam, 2021)
This research aims to determine the students' errors in writing report text at eight grade SMP N 3 Timang Gajah students. The research was conduct using a qualitative approach with a descriptive design. The primary data source is the eighth-grade students and the teacher English at SMP N 3 Timang Gajah. The data collection instrument uses observation sheets, interview sheets, and the documentary (test) study and the researcher's data analysis using Miles and Huberman models, including data reduction, display, and verification. The percentage of grade VIII students' achievement in writing report text in the reference made is low, namely only reaching: general nouns 22.04%, at present tense 22.57%, on linking verbs 29.17% and action verbs are 26.21%. In conclusion, the students still error in writing report text at grade VIII students of SMP N 3 Timang Gajah. Therefore, they should have great motivation and interest in learning report text and get used to practicing it in everyday life.